The Role of Non-routine Problem-solving Skills in Predicting the Metacognitive Habits of Mathematics Teachers in Jordan - Khabour, Omar S.; Al-Zoubi, Ali M. (Dirasat: Educational Sciences, 2023)
Objectives: This study aims to identify the role of solving non-routine mathematics equations in predicting the metacognitive habits of mathematics teachers in Jordan. Methods: The study employed a descriptive analytical approach and was conducted with a sample of 87 eighth-grade mathematics teachers chosen using a systematic random methodology. Two tests were administered: the first assessed the skills of solving non-routine mathematical equations, and the second assessed the metacognitive habits. Results: The results indicated that the skills of solving non-routine mathematical equations can predict the metacognitive habits of eighth-grade mathematics teachers. In addition, the study revealed that the sample’s skill level in solving non-routine mathematical equations and their metacognitive habits were low. Conclusions: The study recommends providing training to mathematics teachers on the skill of mathematical reasoning through the use of non-routine mathematical equations, presenting them as real-life problems. It is worth telling that this approach can contribute to the development of mathematics teachers’ skills.